Analisis Kematangan Emosi Dan Perilaku Agresi Verbal Pada Remaja Di Kota Tomohon - Oktaveri armadi, Andi Arga; Sasuwu, Chrispian Brainerd; Milala, Enta Olivia BR S.; Warawarin, Klaudia; Aditama, Mint Husen Raya; Kasenda, Rinna (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to find out how emotional maturity and verbal aggression are in adolescents in the city of Tomohon, North Sulawesi. This type of research is a type of case study research that uses qualitative methods with an interpretive phenomenological approach. The informants in this study were a group of five youths using a purposive sampling technique to collect informants. Collection techniques, namely observation, interviews, and documentation were carried out to analyze emotional maturity and verbal aggression in a group of adolescents. The results of this study concluded that there was a negative effect between emotional maturity and verbal aggression in a group of adolescents which was inversely proportional, where if the value of emotional maturity went up, the value of aggressiveness would decrease and vice versa. the results of this study concluded that the relationship between emotional maturity and verbal aggression is very significant, meaning that these two things are very strongly related.